2020
DOI: 10.3390/cells9071599
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin Impairs In Vitro Testosterone Production, Sperm Motility, and Fertility in Chicken: Possible Involvement of Its Receptor CMKLR1

Abstract: The chemokine chemerin is a novel adipokine involved in the regulation of energy metabolism but also female reproductive functions in mammals. Its effects on male fertility are less studied. Here, we investigated the involvement of chemerin in chicken male reproduction. Indeed, the improvement of the sperm of roosters is a challenge for the breeders since the sperm quantity and quality have largely decreased for several years. By using specific chicken antibodies, here we show that chemerin and its mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…CMKLR1 is expressed mainly in adipose tissue (higher levels in white compared to brown adipose tissue), bone, lung, brain, heart, and placenta [55,59]. Chemerin binds to orphan CMKLR1 [24,60], activates the three Gαi subtypes, and the two Gαo isoform [56], exercising in this way main biological functions [57,60]. CMKLR1 activation is responsible for intracellular calcium release and a reduction in cAMP (cyclic adenosine monophosphate) accumulation [59].…”
Section: Discussionmentioning
confidence: 99%
“…CMKLR1 is expressed mainly in adipose tissue (higher levels in white compared to brown adipose tissue), bone, lung, brain, heart, and placenta [55,59]. Chemerin binds to orphan CMKLR1 [24,60], activates the three Gαi subtypes, and the two Gαo isoform [56], exercising in this way main biological functions [57,60]. CMKLR1 activation is responsible for intracellular calcium release and a reduction in cAMP (cyclic adenosine monophosphate) accumulation [59].…”
Section: Discussionmentioning
confidence: 99%
“…In chickens, our team demonstrated that plasma chemerin concentrations were negatively associated with egg hatchability, suggesting a potential role of this adipokine on egg and/or embryo development 22 . After in vivo experiments on fresh rooster sperm incubated with recombinant chicken chemerin and used for artificial insemination (AI), we observed a negative effect of chemerin on egg fertility for the first 3 days after AI, suggesting an impact of this hormone on early embryo development (EED) 23 . In addition, in turkeys, we found that chemerin expression in granulosa cells increases in the mature follicle immediately before ovulation, thus, potentially influencing EED 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Like mammals, chemerin and its main receptor CMKLR1 are present in chicken testes with the lowest expression for adult chicken compared to immature animals (Estienne et al, 2020b). Estienne et al have shown that in vitro recombinant chicken chemerin reduced motility of spermatozoa and inhibits testosterone production bythe testes (Estienne et al, 2020b).…”
Section: Reproductive (Gonadal) Functionsmentioning
confidence: 99%
“…Like mammals, chemerin and its main receptor CMKLR1 are present in chicken testes with the lowest expression for adult chicken compared to immature animals (Estienne et al, 2020b). Estienne et al have shown that in vitro recombinant chicken chemerin reduced motility of spermatozoa and inhibits testosterone production bythe testes (Estienne et al, 2020b). They demonstrated that chemerin seminal plasma concentration but not chemerin blood plasma was negatively correlated with spermatozoa concentration and motility in vivo in chicken sperm.…”
Section: Reproductive (Gonadal) Functionsmentioning
confidence: 99%